Evaluation of the chemical and antioxidant properties of wild and cultivated mushrooms of Ghana - Obodai, Mary (2015)
Knowledge of the chemical composition of both wild and cultivated edible mushrooms in Ghana is limited. This study reports their nutritional value, composition in lipophilic and hydrophilic molecules, minerals and antioxidant properties. The samples were found to be nutritionally rich in carbohydrates, ranging from 64.14 ± 0.93 g in Pleurotus ostreatus strain EM-1 to 80.17 ± 0.34 g in Lentinus squarosullus strain LSF. The highest level of proteins (28.40 ± 0.86 g) was recorded in the mentioned P. ostreatus strain. Low fat contents were registered in the samples, with Auricularia auricula recording the lowest value. High levels of potassium were also observed with the following decreasing order of elements: K>P~Na>Mg>Ca. High levels of antioxidants were also observed, thus making mushrooms suitable to be used as functional foods or nutraceutical sources. Furthermore, this study provides new information regarding chemical properties of mushrooms from Ghana, which is very important for the biodiversity characterization of this country.